Gross anatomy of the heart of the alpaca (Vicugna pacos, Linnaeus 1758). (4th December 2017) - Pérez, W.; Méndez, V.; Vazquez, N.; Navarrete, M.; König, H. E.
Summary: The available information about anatomical characteristics of the cardiovascular system of the alpaca ( Vicugna pacos, Linnaeus 1758) is scarce. The general objective of this work was to describe its heart anatomy. We dissected six adult animals and five neonates. The heart of the alpaca was located in the middle mediastinum, with a craniocaudal extension from the third to the sixth rib. No ligament that connected the fibrous pericardium to the sternum or to the diaphragm was detected. In the right atrium, there was a developed crista terminalis and small pectinate muscles. In the right ventricle, the septomarginal trabecula was very large. From the proximities of the interventricular septum arose small septomarginal trabeculae that ended in carnous trabeculae of the septal wall. The left atrium included little developed pectinate muscles. On the left ventricle, both papillary muscles were bilobed. Two left septomarginal trabeculas were detected in this ventricle. The left subclavian artery was originated from the aortic arch separately from the brachiocephalic trunk, and bicarotid trunk was present. The other branches of the subclavian artery were similar to the domestic ruminants. The arterial supply of the heart was of the right type. In conclusion, the heart anatomy of alpaca and the irrigation of thoracic cavity were more similar to those of old world camels and different from domestic ruminants.